2018
DOI: 10.1155/2018/8084127
|View full text |Cite
|
Sign up to set email alerts
|

Feed Additives Produced on the Basis of Organic Forms of Micronutrients as a Means of Biofortification of Food of Animal Origin

Abstract: In recent years, there has been a steadily growing demand for animal protein. Consumer awareness is also growing every year, which is why breeders are obliged to provide animals with the best possible environmental conditions that will determine the productivity of animals and the quality of raw materials obtained from them. Today's consumer is looking for not only the highest quality food but also the one that will characterize health-promoting properties.erefore, food is sought, which will be characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Загальновідомо, що мікроелементи не можуть бути синтезовані в організмі чи замінені іншими речовинами, тому основним джерелом надходження їх в організм сільськогосподарської птиці є корми (Górniak et al, 2018;Nys et al, 2018). Вітчизняний та зарубіжний досвід переконливо доводять, що введення в комбікорми для сільськогосподарської птиці мікроелементів в оптимальних кількостях і співвідношеннях дозволяє не тільки підвищити її продуктивність і життєздатність, а й поліпшити конверсію корму та якість продукції.…”
Section: вступunclassified
“…Загальновідомо, що мікроелементи не можуть бути синтезовані в організмі чи замінені іншими речовинами, тому основним джерелом надходження їх в організм сільськогосподарської птиці є корми (Górniak et al, 2018;Nys et al, 2018). Вітчизняний та зарубіжний досвід переконливо доводять, що введення в комбікорми для сільськогосподарської птиці мікроелементів в оптимальних кількостях і співвідношеннях дозволяє не тільки підвищити її продуктивність і життєздатність, а й поліпшити конверсію корму та якість продукції.…”
Section: вступunclassified
“…Advanced studies were carried out for the application of mixed nutrients in crops. Recently, Górniak et al [11] reported the studies in the field of biofortification of edible plants with selenium and iodine. Another factor that contributes towards the nutrient intake in the human body is whether the food consumed supplies micronutrient form in bioavailable form.…”
Section: Introductionmentioning
confidence: 99%
“…A, B 1 , B 6 , and B 12 ) and essential fatty acids (Średnicka-Tober et al ., 2016). In addition, beef as well as milk are at the forefront of consumed animal products (Górniak et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%